The importance of geotechnical knowledge of terrains: Beja municipality, Alentejo, Portugal - Soares, Sofia (2017)
The municipality of Beja, in Alentejo (Portugal), is presented as a case in which the insufficient knowledge of the geological and geotechnical characteristics of terrains contributes to serious problems in the establishment of building platforms. In Beja three main geotechnical units can be defined: fills, residual soils from gabbro-diorite weathering and gabbro-diorite bedrock. The knowledge of location, thickness and geotechnical properties of all these formations will contribute to the accurate engineering design and construction work, and also to support urban planning and therefore to minimize geological risk by avoiding zones with thick problematic soils as shown with a case study.